2018
DOI: 10.25248/reas.e125.2019
|View full text |Cite
|
Sign up to set email alerts
|

Perfil epidemiológico da hipertensão arterial sistêmica em uma população da zona urbana do Maranhão

Abstract: Objetivos: Traçar o perfil epidemiológico da Hipertensão Arterial Sistêmica em uma população de zona urbana.  Métodos: Estudo descritivo, transversal, com abordagem quantitativa, desenvolvido nas unidades básicas de saúde (UBS) da zona urbana do município de Aldeias Altas-MA. A amostra foi composta por 228 hipertensos cadastrados no programa Hiperdia e acompanhados pela Estratégia Saúde da Família Resultados: O perfil predominantemente encontrado no estudo revelou indivíduos hipertensos do sexo feminino, raça/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0
9

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 0 publications
0
2
0
9
Order By: Relevance
“…The increased overweight index, verified in this study leads us to infer that it is necessary to carry out activities that encourage healthy habits for the patients of the UBS surveyed, considering that sedentary lifestyle is a risk factor for cardiovascular disease, as well as for SAH and DM (Castro et al, 2019). Research, Society andDevelopment, v. 9, n. 10, e6019108986, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i10.8986 Regarding abdominal circumference, 67 (48.91%) women had values> 88, presenting above normal standards, and 24 (17.52%) of men had circumference <102, within normal limits * (Graph 5).…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…The increased overweight index, verified in this study leads us to infer that it is necessary to carry out activities that encourage healthy habits for the patients of the UBS surveyed, considering that sedentary lifestyle is a risk factor for cardiovascular disease, as well as for SAH and DM (Castro et al, 2019). Research, Society andDevelopment, v. 9, n. 10, e6019108986, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i10.8986 Regarding abdominal circumference, 67 (48.91%) women had values> 88, presenting above normal standards, and 24 (17.52%) of men had circumference <102, within normal limits * (Graph 5).…”
Section: Resultsmentioning
confidence: 55%
“…Another municipality in Pernambuco showed that of the 35,596 registered hypertensive patients, 65% were women (Lima, Gaia, & Ferreira, 2012 The study showed that, in the researched field, there is a higher prevalence of these pathologies in individuals aged between 60 and 69 years, followed by individuals aged between 50 and 59. This is explained by the fact that there is a higher prevalence in cases of hypertension in patients older than 50 years; it is stipulated that 65% of the elderly have this systemic pathology and is directly related to the most advanced age groups (Castro et al, 2019). Bearing in mind that it is proven that the patient who has one of these pathologies is more likely to develop the other (Fonsêca, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…A HAS foi mais prevalente nas faixas etárias de 61 a 70 anos (32%) e de 71 a 80 anos (27%), No gênero feminino a HAS foi observada a partir dos 20 anos e apresentou dois picos de incidência, dos 41 aos 50 anos e dos 61 aos 70 anos e apresentando redução drástica (P < 0,05) após os 80anos, enquanto no gênero masculino ela foi observada apenas após os 51 anos, apresentando aumento significativo (P<0,05) dos 61 aos 70 anos e depois redução drástica (P < 0,05) (Figura 2). Acredita-se que isto tenha ocorrido porque até os 50 anos os homens não costumam procurar os serviços de saúde, ao contrário das mulheres que buscam acompanhamento médico com maior frequência o que aumenta o diagnóstico de doenças crônicas (CASTRO et al, 2018;VILLELA et al, 2018;SOUSA et al, 2019). Estes resultados discordaram de trabalhos anteriores que observaram menor prevalência de mulheres hipertensas até os 60 anos e concordaram que após os 60 anos as taxas podem se igualar ou ficar maiores nas mulheres (HARVEY et al, 2015;ZDROJEWSKI et al, 2016;SOUSA et al, 2019).…”
Section: Resultsunclassified
“…Figura 1 -Perfil etário dos hipertensos do município de Paulo Afonso (BA), no período de 30 de maio a 30 de junho de 2019. OLIVEIRA et al, 2013;RADOVANOVIC et al, 2014;CASTRO et al, 2018). Os resultados referentes a renda confirmaram as observações de Malta et al (2011), de que as classes mais abastadas não buscam os serviços públicos de saúde para acompanhamento da HAS e reafirmam a relação entre as desigualdades sociais e os determinantes de saúde.…”
Section: Resultsunclassified
See 1 more Smart Citation